The specificity of the neural response to speech at birth. Issue 3 (15th May 2017) - May, Lillian; Gervain, Judit; Carreiras, Manuel; Werker, Janet F.
Abstract: In this work we ask whether at birth, the human brain responds uniquely to speech, or if similar activation also occurs to a non‐speech surrogate 'language'. We compare neural activation in newborn infants to the language heard in utero (English), to an unfamiliar language (Spanish), and to a whistled surrogate language (Silbo Gomero) that, while used by humans to communicate, is not speech. Anterior temporal areas of the neonate cortex are activated in response to both familiar and unfamiliar spoken language, but these classic language areas are not activated to the whistled surrogate form. These results suggest that at the time human infants emerge from the womb, the neural preparation for language is specialized to speech. Abstract : Anterior temporal areas of the neonate cortex are activated in response to both familiar and unfamiliar spoken language, but these classic language areas are not activated to whistled surrogate language.